2019
DOI: 10.3389/fnint.2019.00029
|View full text |Cite
|
Sign up to set email alerts
|

PET Measures of D1, D2, and DAT Binding Are Associated With Heightened Tactile Responsivity in Rhesus Macaques: Implications for Sensory Processing Disorder

Abstract: Sensory processing disorder (SPD), a developmental regulatory condition characterized by marked under- or over-responsivity to non-noxious sensory stimulation, is a common but poorly understood disorder that can profoundly affect mood, cognition, social behavior and adaptive life skills. Little is known about the etiology and neural underpinnings. Clinical research indicates that children with SPD show greater prevalence of difficulties in complex cognitive behavior including working memory, behavioral flexibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 131 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…Together, these findings indicate that dopamine neurons underlie (i) the subjective experience of the perceived, rather than mere sensory, aspects of tactile signals and (ii) the regulation of inherent uncertainty during perceptual processing and inference. Furthermore, evidence from a recent receptor imaging study (Schneider et al, 2019) with a larger sample of monkeys also shows that the binding potentials of dopamine receptors (D1 and DAT) correlate with behavioral responsivity to tactile stimuli. Human pharmacological research also found that increasing the level of monoamines in the brain by administering amphetamine increases perceptual and cortical plasticity of tactile learning (Dinse et al, 2003).…”
Section: Dopaminergic Modulation Of Tactile Perceptionmentioning
confidence: 97%
“…Together, these findings indicate that dopamine neurons underlie (i) the subjective experience of the perceived, rather than mere sensory, aspects of tactile signals and (ii) the regulation of inherent uncertainty during perceptual processing and inference. Furthermore, evidence from a recent receptor imaging study (Schneider et al, 2019) with a larger sample of monkeys also shows that the binding potentials of dopamine receptors (D1 and DAT) correlate with behavioral responsivity to tactile stimuli. Human pharmacological research also found that increasing the level of monoamines in the brain by administering amphetamine increases perceptual and cortical plasticity of tactile learning (Dinse et al, 2003).…”
Section: Dopaminergic Modulation Of Tactile Perceptionmentioning
confidence: 97%